Peritumoral Imaging Manifestations on Gd-EOB-DTPA-Enhanced MRI for Preoperative Prediction of Microvascular Invasion in Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis - Wu, Ying; Zhu, Meilin; Liu, Yiming; Cao, Xinyue; Zhang, Guojin; Yin, Longlin (Frontiers in Oncology, 2022)
PURPOSE The aim was to investigate the association between microvascular invasion (MVI) and peritumoral imaging features of gadolinium ethoxybenzyl DTPA-enhanced magnetic resonance imaging (Gd-EOB-DTPA-enhanced MRI) in hepatocellular carcinoma (HCC). METHODS Up until Feb 24, 2022, the PubMed, Embase, and Cochrane Library databases were carefully searched for relevant material. The software packages utilized for this meta-analysis were Review Manager 5.4.1, Meta-DiSc 1.4, and Stata16.0. Summary results are presented as sensitivity (SEN), specificity (SPE), diagnostic odds ratios (DOR), area under the receiver operating characteristic curve (AUC), and 95% confidence intervals (95% CI). The sources of heterogeneity were investigated using subgroup analysis. RESULTS An aggregate of nineteen articles were remembered for this meta-analysis: peritumoral enhancement on arterial phase (AP) was described in 13 of these studies and peritumoral hypointensity on hepatobiliary phase (HBP) in all 19 studies. The SEN, SPE, DOR and AUC of the 13 investigations on peritumoral enhancement on AP were 0.59 (95% CI, 0.41‒0.58), 0.80 (95% CI, 0.75‒0.85), 4 (95% CI, 3‒6), and 0.73 (95% CI, 0.69‒0.77), respectively. The SEN, SPE, DOR and AUC of 19 studies on peritumoral hypointensity on HBP were 0.55 (95% CI, 0.45‒0.64), 0.87 (95% CI, 0.81‒0.91), 8 (95% CI, 5‒12), and 0.80 (95% CI, 0.76‒0.83), respectively. Subgroup analysis of two imaging features identified nine and six potential factors for heterogeneity, respectively. CONCLUSION The results of peritumoral enhancement on AP and peritumoral hypointensity on HBP showed high SPE but low SEN. This indicates that the peritumoral imaging features on Gd-EOB-DTPA-enhanced MRI can be used as a noninvasive, excluded diagnosis for predicting hepatic MVI in HCC preoperatively. Moreover, the results of this analysis should be updated when additional data become available. And in the future, how to improve its SEN will be a new research direction.